Scaling up zinc treatment for childhood diarrhoea in the developing country setting: a before‐ and after‐intervention study. (12th September 2016) - Nunan, Michael; Horoto, William; Manea, Timmy; Duncan, Greg; Duke, Trevor
Abstract: Introduction: Zinc sulphate is an important intervention for the treatment of diarrhoea in children in developing countries. We undertook a series of interventions to increase the availability and usage of zinc sulphate at primary healthcare facilities in the Solomon Islands. Methodology: A 12 month before‐and‐after intervention effectiveness trial in 80 randomly selected clinics. Data was collected on whether children <5 years old with diarrhoea had received zinc. Data was also collected on other medications received, the availability of zinc and staff comprehension. A series of interventions was implemented by the National Pharmacy Services Division. Results: The mean usage of zinc sulphate increased by 191.2% over baseline; from 106/771 (13.7%) at baseline to 283/710 (39.9%) (p < 0.05, χ 2 ) at follow‐up; the use of oral rehydration salts (ORS) did not decrease. The availability of zinc sulphate increased from 3/77 clinics (3.9%) to 61/69 clinics (88.4%) (p < 0.05). Summary: Low‐cost interventions can improve the usage of zinc sulphate in the Pacific island setting. This paper provides a model for other countries to increase uptake of zinc sulphate and other interventions at the primary healthcare level.